Space-based quantification of per capita CO2 emissions from cities - Dien Wu; John C Lin; Tomohiro Oda; Eric A Kort (Environmental Research Letters, 2020)
Urban areas are currently responsible for ∼70% of the global energy-related carbon dioxide (CO _2 ) emissions, and rapid ongoing global urbanization is increasing the number and size of cities. Thus, understanding city-scale CO _2 emissions and how they vary between cities with different urban densities is a critical task. While the relationship between CO _2 emissions and population density has been explored widely in prior studies, their conclusions were sensitive to inconsistent definitions of urban boundaries and the reliance upon CO _2 emission inventories that implicitly assumed population relationships. Here we provide the first independent estimates of direct per capita CO _2 emissions ( E _pc ) from spaceborne atmospheric CO _2 measurements from the Orbiting Carbon Observatory-2 (OCO-2) for a total 20 cities across multiple continents. The analysis accounts for the influence of meteorology on the satellite observations with an atmospheric model. The resultant upwind source region sampled by the satellite serves as an objective urban extent for aggregating emissions and population densities. Thus, we are able to detect emission ‘hotspots’ on a per capita basis from a few cities, subject to sampling restrictions from OCO-2. Our results suggest that E _pc declines as population densities increase, albeit the decrease in E _pc is partially limited by the positive correlation between E _pc and per capita gross domestic product. As additional CO _2 -observing satellites are launched in the coming years, our space-based approach to understanding CO _2 emissions from cities has significant potential in tracking and evaluating the future trajectory of urban growth and informing the effects of carbon reduction plans.